2013
DOI: 10.3390/molecules181214797
|View full text |Cite
|
Sign up to set email alerts
|

New Short Strategy for the Synthesis of the Dibenz[b,f]oxepin Scaffold

Abstract: Abstract:In this report a short and efficient synthesis of the dibenz[b,f]oxepin framework through intramolecular S N Ar and McMurry reactions is described. The diaryl ethers required for the McMurry reaction have been obtained in good yields under microwave-assisted conditions of the reaction of salicylaldehydes with fluorobenzaldehydes without catalysts. Application of an intramolecular McMurry reaction to the synthesized diarylethers using TiCl 4 /Zn in THF gave the target dibenzo [b,f]oxepin system in 53%-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…[ 130 ] Moreno et al in 2013 demonstrated synthesis of the dibenz[ b , f ]oxepines 373 through S N Ar reaction of salicylaldehydes 49 with fluorobenzaldehydes 47 and then intramolecular McMurry reaction of the prepared 2,2′‐oxybis(benzaldehyde) compounds 372 using TiCl 4 /Zn (Scheme 88). [ 131 ]…”
Section: Titanium‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 130 ] Moreno et al in 2013 demonstrated synthesis of the dibenz[ b , f ]oxepines 373 through S N Ar reaction of salicylaldehydes 49 with fluorobenzaldehydes 47 and then intramolecular McMurry reaction of the prepared 2,2′‐oxybis(benzaldehyde) compounds 372 using TiCl 4 /Zn (Scheme 88). [ 131 ]…”
Section: Titanium‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…[130] McMurry reaction of the prepared 2,2 0 -oxybis(benzaldehyde) compounds 372 using TiCl 4 /Zn (Scheme 88). [131] Tamura et al in 2010 reported a multistep way for the synthesis of bauhinoxepin J 379 from 2,5-dihydroxyp-benzoquinone 374 as starting material. [132] In this synthetic method, Ti-Zr McMurry coupling of tetramethoxybenzaldehyde 375 with salicylaldehyde 49 followed by hydrogenation, DDQ oxidative dearomatization, and final cyclization reaction afforded the dibenzo[b,f]oxepine scaffold (Scheme 89).…”
Section: Titanium-catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…Very few MW-assisted syntheses of dibenzoxazepines have been reported. Nevertheless, two very interesting approaches, based (i) on an intramolecular SNAr; and (ii) on a McMurry reaction, each occurring with MW-activation, have been described by Moreno and co-workers [29] (Scheme 10A). The dibenz [b,f ]oxepines are characterized by an oxepane fused with two aromatic moieties: this is a relevant pharmacophore present in the structure of numerous therapeutic agents which can be used for several therapeutic applications such as antidepressant, antipsychotic and anti-inflammatory indications ( Figure 5) [24][25][26][27][28].…”
Section: Oxepanes Thiepanes and Their Derivativesmentioning
confidence: 99%
“…Very few MW-assisted syntheses of dibenzoxazepines have been reported. Nevertheless, two very interesting approaches, based (i) on an intramolecular SNAr; and (ii) on a McMurry reaction, each occurring with MW-activation, have been described by Moreno and co-workers [29] (Scheme 10A). Very few MW-assisted syntheses of dibenzoxazepines have been reported.…”
Section: Oxepanes Thiepanes and Their Derivativesmentioning
confidence: 99%
See 1 more Smart Citation